Social activity is a factor of the Russian ecovillages’ self-organization - M. Y. Shchukina (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2014)
Using example of the Russian ecovillages it is shown that a necessary condition for the formation and intensification of local communities and factor of their successful selforganization is a social activity of the ecovillage residents. It is proposed an approach to the consideration of eco-villages as subjects of sustainable rural development in order to implement their civic initiatives in the territorial public self-government. There is a need to integrate eco-villages in rural settlements that has a great political importance for the sustainable rural development, the provision of public territorial control, the preservation of socio-cultural identity and the country's food security.